Sedimentology of the Grønfjorden Bed and associated sedimentary deposits: Grønfjorden, Svalbard - Berg, Tor Kristian (The University of Bergen, 2018)
The Grønfjorden Bed represents the earliest Paleogene sedimentary deposits in the Central Tertiary Basin on Spitsbergen. It has a patchy distribution, and consists of conglomerates and sandstones of fluvial origin that rest unconformably upon Lower Cretaceous strata. The Grønfjorden Bed is a sub-unit of the coal-bearing Todalen Member of the Firkanten Formation, and has received limited emphasis due to the attention received by the productive coal seams higher up in the stratigraphy. This study has investigated the Grønfjorden Bed and associated sedimentary deposits in detail through the use of conventional sedimentary logging and remote photography and photogrammetric modelling. The photogrammetric models have provided virtual outcrops on which detailed sedimentological analysis has been performed. On the basis of detailed facies analysis, three facies associations were recognized: deposits of gravel-bed fluvial channel environment, deposits of sand-bed fluvial channel environment and deposits of a floodplain environment. The study supports previous interpretations of a fluvial depositional environment that was gradually flooded by an elevation in the groundwater table as a response to the initial Paleogene transgression. The study presents evidence of a northwest towards the southeast paleocurrent direction for the fluvial conglomerates and sandstones. This ties well together with previous studies from nearby exposures, and suggests the presence of a wide fluvial valley in the Grønfjorden area at the time of deposition. The paleocurrent direction of the fluvial valley further coincides with the provenance of the conglomeratic clasts suggesting a source to the west and northwest. The study suggests that the initial fluvial environment contributed as a tributary valley to a much larger fluvial valley system evident by the presence of the Grønfjorden Bed and also swell and depression topography of the unconformity. The study as a whole improves the general understanding of the Grønfjorden Bed depositional ...